Digital Customer Experience and Brand Loyalty: Mediating Engagement and Moderating Authenticity Among Generation Z - Jamaluddin Dahlan jamaluddin; asraf yunus (LP2M IAIN Palopo, 2026)
Grounded in the stimulus–organism–response paradigm, this study examines how digital customer experience (DCE) shapes brand loyalty (BL) among Generation Z social-commerce consumers, testing brand engagement (BE) as a mediating mechanism and brand authenticity (BA) as a moderating boundary condition. Survey data were collected from 384 Generation Z Shopee consumers across Kendari City, Konawe Regency, and Kolaka Regency, Indonesia, and analyzed using partial least squares structural equation modeling. Results show that DCE significantly predicts both BE and BL directly, that BE significantly and partially mediates the DCE–BL relationship, and that BA exerts a significant direct effect on BL but does not significantly moderate the BE–BL relationship. Theoretically, this study contributes an integrated test combining the stimulus–organism–response paradigm, consumer brand engagement theory, and brand authenticity theory within one moderated-mediation model, providing statistically decisive evidence that brand authenticity operates as an independent driver of loyalty rather than a condition strengthening engagement's effect, narrowing an unresolved debate over authenticity's structural role in recent social-commerce literature. Practically, brands should treat experience quality and authenticity-building as parallel, independently justified investments rather than assuming authenticity multiplies engagement's returns. These results extend social-commerce loyalty research to an underrepresented, non-metropolitan Indonesian context.